2011
DOI: 10.1159/000329557
|View full text |Cite
|
Sign up to set email alerts
|

Early Postnatal Surge of Serum Clara Cell Secretory Protein in Newborn Infants

Abstract: Background: Clara cell secretory protein (CCSP) is an anti-inflammatory mediator, but its role in neonatal lung adaptation and diseases is uncertain. Objective: To characterize postnatal changes in serum CCSP in relation to gestation, respiratory disease (RDS) and bronchopulmonary dysplasia (BPD) in comparison with other anti-inflammatory cytokines (IL-4, -10 and -13). Methods: Blood was collected from 76 infants (26 of 23–29 weeks’ gestation, 33 of 30–36 weeks’ gestation and 17 term infants) at birth (preterm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
14
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 38 publications
3
14
0
Order By: Relevance
“…This pilot study is in agreement with previous studies for preterm infants [14, 23] but provides further evidence for term infants. Furthermore, CC16 levels at birth were found to positively correlate with BPD diagnosis and negatively with severity.…”
Section: Discussionsupporting
confidence: 93%
“…This pilot study is in agreement with previous studies for preterm infants [14, 23] but provides further evidence for term infants. Furthermore, CC16 levels at birth were found to positively correlate with BPD diagnosis and negatively with severity.…”
Section: Discussionsupporting
confidence: 93%
“…Previous work suggested that there is a postnatal surge of [CC10] peaking 12-24 h after birth and falling thereafter [2,8]. Our study was not designed to replicate these findings since our numbers at each time point were small, and we could have missed such a finding.…”
Section: Discussionmentioning
confidence: 84%
“…We found that CC10 is detectable in all three compartments, with the least amount in the stool. Previous studies evaluating serum [CC10] in term infants primarily examined infants with respiratory illness, thus making these values harder to interpret [2,8]. Serum CC10 is known to increase when lung injury is present due to increased CC10 leakage across the bronchoalveolar/blood barrier [10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ogihara et al [14] suggested that prenatal lung injury has a priming effect, increasing the susceptibility of fetal lungs to subsequent toxic agents. Loughran-Fowlds et al [23] also found that infants who developed BPD had persistently lower serum CC16 levels at 12 hours compared with those who did not develop BPD. However, Sarafidis et al [17] found significantly higher CC16 concentrations at 14 days in ventilated infants who developed BPD than in nonventilated infants who did not develop BPD.…”
Section: Discussionmentioning
confidence: 99%